FUTURE PROSPECT OF CDM SOLAR COOKER PROJECT ACEH 1, INDONESIA - suharta, herliyani (Agency for the Assessment and Application of Technology)
Firewood in almost all rural areas uses firewood for cooking. Smoke exposure from firewood seriously affects the children's growth and the health of women, increasing woman burden and poverty. Its greenhouse gas (GHG) emissions contribute to global climate change. This is one of the greatest challenges of humanity. The CDM (Clean Development Mechanism) Solar Cooker Project in Sabang Islands and Badar city in South East Aceh was arranged to lay down a better energy path scenario for the future. Solar concentrator cookers